Frequency of Congenital Anomalies in Newborns and Its Relation to Maternal Health in a Tertiary Care Hospital in Peshawar, Pakistan - Adnan Khan; Muhammad Zuhaid; Maria Fayaz; Faryal Ali; Arsalan Khan; Raza Ullah; Javariya Zafar; Hakeem Ullah; Saiqa Baloch; Sanam Gandapur (University Library System, University of Pittsburgh, 2015)
Background: Congenital anomalies are a major cause of perinatal and neonatal deaths, both in low- and high-income countries. They are relatively common worldwide, affecting 3% to 5% of live births. Methods: A cross-sectional study was conducted from January 2014 to June 2014 at the Khyber teaching hospital in Peshawar. Specific patient information was obtained from patient records at the beginning of the study. Those individuals found to have at least one birth defect were approached and their attendants (mothers) were interviewed. Information regarding various risk factors was collected. Descriptive analyses were carried out. Results: Out of 1062 deliveries, 2.9% (31) of newborns had various congenital anomalies. Hydrocephalus (22.6%), anencephaly (12.9%), and spina bifida (9.7%) were major anomalies. The maternal age ranged from 18 years to 46 years (mean: 30 ± 8). Most of the anomalies (35.5%) were present in the 26-30 years age group. Out of 31 babies, 6.4% had multiple anomalies. The preponderance of various congenital anomalies was seen in parity 1 (35.4%); parities 2 to 4 had lower incidences (35.4%). The consanguinity rate was 67.7%; only 32.3% of patients were using folic acid. History of passive smoking was positive in 16.1% of cases. Conclusion: Anencephaly and hydrocephalus were the most prominent anomaly detected; early prenatal diagnosis may be helpful in decreasing mortality by offering early termination. Low intake of folic acid and a high consanguinity rate were the most common associated risk factors for congenital anomalies. These risk factors may be reduced by creating awareness regarding the avoidance of consanguineous marriage and promoting the use of folic acid during pregnancy.